High-resolution spectroscopy and global analysis of CF4 rovibrational bands to model its atmospheric absorption. (November 2017) - Carlos, M.; Gruson, O.; Richard, C.; Boudon, V.; Rotger, M.; Thomas, X.; Maul, C.; Sydow, C.; Domanskaya, A.; Georges, R.; Soulard, P.; Pirali, O.; et al.
Highlights: Global analysis of many rovibrational bands of CF4 . This allows to simulate hot bands in the strongly absorbing 3μm region. The results allow to model 92% of the atmospheric absorption of this greenhouse gas. They have been used for spectroscopic database updates, including HITRAN2016. Abstract: CF4, or tetrafluoromethane, is a chemically inert and strongly absorbing greenhouse gas, mainly of anthropogenic origin. In order to monitor and reduce its atmospheric emissions and concentration, it is thus necessary to obtain an accurate model of its infrared absorption. Such models allow opacity calculations for radiative transfer atmospheric models. In the present work, we perform a global analysis (divided into two distinct fitting schemes) of 17 rovibrational bands of CF4 . This gives a reliable model of many of its lower rovibrational levels and allows the calculation of the infrared absorption in the strongly absorbing ν 3 region (1283 cm − 1 / 7.8 μm), including the main hot band, namely ν 3 + ν 2 − ν 2 as well as ν 3 + ν 1 − ν 1 ; we could also extrapolate the ν 3 + ν 4 − ν 4 absorption. This represents almost 92% of the absorption at room temperature in this spectral region. A new accurate value of the C–F bond length is evaluated to r e = 1.314860 ( 21 ) Å. The present results have been used to update the HITRAN, GEISA and TFMeCaSDa (VAMDC) databases.